FORECASTING OF EXPLORATION OF THE URANIUN MINERALIZATION IN THE SOUTH-WESTERN PART OF THE UKRAINIAN SHIELD ON THE BASE OF WATERHELIUM SERVES - KOVAL, V.; DIMITROV, G.; MAKARENKO, N. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Spatial coincidence helium heightened concentration with uranium mineralization zones and on the place gold-ove manifestations was established. The study of quantitative connectio intensity of helium anomalies showed that correlative connection are between these parameters. With the help of watergelium serves it can be received additional facts which defined the connection uranium mineralization with definite structures and new potentially uranium-bearing areas can be outline.